Exercising Control: A Comparative Study of Government Agencies and their Relationships with the Public Using Social Media - Unsworth, Kristene; Axelsson, Ann-Sofie; Goggins, Sean; Mascaro, Christopher (AoIR Selected Papers of Internet Research, 2012)
We frame the exercise of control through social media not as power-over or oppression, but in its broader sense, as purposive influence toward a predetermined goal. We focus on one growing channel of control; social media use for official communication between government agencies and the public. This paper introduces a framework for analyzing social media use and interaction between government agencies and the public, focusing on a comparative analysis of two consumer protections agencies; one, the Konsumentverket in Sweden, the second, the Consumer Financial Protection Bureau in the US. Contrasting the efficacy and practices associated with social media as a communication tool for citizens and their governments in different societies may lead to important insights regarding local and global applications of new media. The proposed framework is grounded in the concept of active co-construction of reality via Giddens structuration theory, as expanded on by Orlikowski. While this provides a useful lens for understanding the construction of government and public interaction, it does not provide a methodology for examining the discourse in action. To do this we embed critical discourse analysis in structuration theory and use algorithms and methods from social media research (group informatics and TwitterZombie) to collect data and identify social networks. The analysis includes examinations of the written policy as well as the discourse or text published via Twitter and Facebook. In this paper we present our synthesis of structuration theory, computational social science and social media research that emerges from our dozens of empirical studies in these domains over the past seven years. We introduce the resulting approach to the study of technologies of control as a proposed foundation for future empirical work designed to validate the proposed methodology. Future work will implement the methodology and ask how social media is being used to help government agencies achieve their goals.